Distant Ureteral Metastasis from Colon Adenocarcinoma: Report of a Case and Review of the Literature - Ferakis Nikolaos; Anastasopoulos Panagiotis; Bouropoulos Konstantinos; Samaras Vassilios; Poulias Iraklis (Case Reports in Urology)
Carcinomas arising from organs neighbouring the ureter can directly infiltrate the ureter. Distant ureteral metastasis from colon adenocarcinoma is extremely rare and usually an incidental finding in performed autopsies. We report a case of a right ureteral metastasis in a 65-year-old Caucasian male with a history of rectal cancer for which he had been treated 4 years before. He presented with asymptomatic moderate right hydronephrosis. The patient underwent a right nephroureterectomy. Histology of the ureter revealed transmural adenocarcinoma with infiltration of the mucosa. Infiltration of the muscular coat of the bladder was found 2 years later. Thus, cystectomy and left ureterocutaneostomy were performed. The patient died 6 months later due to toxic megacolon during chemotherapy. The differential diagnosis of ureteral adenocarcinoma, especially in patients with previous history of colon adenocarcinoma, should include the possibility of distant metastasis from the primary colonic tumor.